Work-family conflict and organisational commitment amongst fathers in the South African National Defence Force - Rangongo, Matsatsi (Organisational Psychology, 2024)
There is a conceptual and empirical underrepresentation of working fathers in the workfamily literature. Fathers are increasingly encouraged to help raise their children, assume parental responsibilities, and assert parental rights. Many organisations, even the military, are trying to assist workers in balancing work and family obligations. The expectation is that the effective management of work-family conflict will result in positive organisational outcomes, such as organisational commitment. Thisstudy examines the relationship between work-family conflict and three components of organisational commitment (affective, continuance, and normative) among fathers in the South African National Defence Force. Data was collected using a paper-based survey. After data cleaning, there were 132 usable questionnaires from uniformed members of the SA National Defence Force (9 SAI) based in Cape Town.The correlation analysis revealed no significant relationships, with medium to large effects, between work-family conflict and any of the organisational commitment dimensions. Contrary to expectations, the regression results indicate that work-family conflict does not explain significant variance in affective commitment. Work-family conflict also explains significant variance in continuance and normative commitment. Moderation analysis, using PROCESS, showed that neither marital status nor deployment history moderates the relationship between work-family conflict and any component of organisational commitment.